Effects of stratified mass selection on two corn populations and on heterosis of their crosses - Valois, Afonso Celso Candeira; Vencovsky, Roland (Pesquisa Agropecuaria Brasileira, 2014)
The aim of this research was to investigate the effects of stratified mass selection on two corn (Zea mays L.) populations, namely Dante Paulista and Cateto Minas Gerais, and on the performance of the hybrids between these populations in different stages of selection. Dente Paulista was submitted to five cycles of selection and Minas Gerais to three cycles. Yield trials in lattice designs were conducted at three locations totalizing four different environments and thirty-two replications. Appropriate mathematical models were apllied for the analysis of yield values and to investigate the effects of selection on heterosis and the changes of hybrid performances. The result showed that the recurrent intrapopulational selection applied reflected negatively on yield of the population crosses in more advanced stages of selection.